Search, Bargaining, and Employer Discrimination - Åsa Rosén (Uppsala University, Department of Economics, 2001)
This paper analyses Beckers (1971) theory of employer discrimination within a search and wage-bargaining setting. Discriminatory firms pay workers who are discriminated against less, and apply stricter hiring-criteria to these workers. It is shown that the highest profits are realized by firms with a positive discrimination coefficient. Moreover, once ownership and control are separated, both highest profits and highest utility may be realized by firms with a positive discrimination coefficient. Thus, market forces, like entry and/or takeovers do not ensure that wage differentials due to employer discrimination will disappear.
urn:nbn:se:uu:diva-2420
Keywords: J71; 330; Search; discrimination